Creating instructional materials - Bullough, Robert V. (United States of America: Charles E. Merrill Publishing Company, 1978)
This text can be used as the basis for a course, or as a source book that offers self-contained chapters which are based on individual production process. A bibliography has been provided that includes book and articles that will serve as a source of additional information in the many fields that are encompassed by instructional media.
1. A Basis for the Design and Selection of Media -- 2. Picture Preservation -- 3. Illustrations -- 4. Lettering Techniques -- 5. Visual Design -- 6. Poster, Charts and Graphs -- 7. Copying and Duplicating Process -- 8. Overhead Transparencies -- 9. Display and Demonstration Board -- 10. Three-Dimensional Teaching Devices -- 11. Photography -- 12. Audio Techniques -- 13. Television .
Includes index.
Keywords: TEACHING MATERIALS; TEACHING -- AIDS AND DEVICES